2008
DOI: 10.4103/1817-1737.43083
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid- and ethambutol-induced psychosis

Abstract: Most cases of antituberculous agent–associated psychoses were caused by isoniazid (INH), with ethambutol (EMB)-induced psychosis being rare. The concomitant occurrence of INH- and EMB- induced psychosis and in a single individual is extremely uncommon. We report a case of 28-year-old male who developed psychotic symptoms on start of EMB initially and later on INH also. He was prescribed rifampicin, pyrazinamide, and ofloxacin and had no further psychotic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…Many anti-TB agents are known to be cause of psychiatric adverse events i.e. isoniazid [10], ciprofloxacin [11], ethambutol [10], ethionamide [12] and cycloserine [8,[13][14][15][16], in this case the culprit drug was cycloserine. Therefore, the administration of cycloserine was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Many anti-TB agents are known to be cause of psychiatric adverse events i.e. isoniazid [10], ciprofloxacin [11], ethambutol [10], ethionamide [12] and cycloserine [8,[13][14][15][16], in this case the culprit drug was cycloserine. Therefore, the administration of cycloserine was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Isoniazid also has an antidepressant effect, and was one of the first antidepressants discovered. [1][2][3][4][5][6][7][8] To the best of our knowledge, no cases of isoniazidinduced delirium (with all clinical features of delirium according to DSM-IV criteria) have ever been described in the literature. Peripheral neuropathy and central nervous system effects (dysarthria, seizures, dysphoria, and irritability) have also been described.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] On the basis of this hypothesis, isoniazid therapy was stopped and substituted with moxifloxacin; sedative therapy was also progressively reduced to haloperidol 1 mg and delorazepam 1 mg once every 2 days. Among isoniazid side effects, central nervous system alterations, such as psychosis, psychomotor agitation, and drowsiness are described, although rare.…”
Section: Case Reportmentioning
confidence: 99%
“…However, information about this issue is still limited, and it is reported generally as case reports (4,6,7). Additionally, Jackson defined in 1957 five psychiatric cases related to INH treatment, in two of which paranoid delusion were prominent (5).…”
Section: Discussionmentioning
confidence: 99%
“…INH induced psychotic diseases are rarely encountered, and the most common ones are psychosis, obsessive-compulsive disease, and mania (3). The exact mechanism of INH induced psychosis is unknown, but it has been suggested that as INH interacts with various metabolites which are necessary for normal functions of neurons, it may lead to psychosis depending problems caused by these mechanisms (4). In this case presentation, a 28 years old male patient who developed acute psychotic attack under INH treatment is reported.…”
Section: Introductionmentioning
confidence: 98%